Intricacies of Imposter Phenomenon, Mental Well-Being, Self-Compassion and Academic Integrity Interactions Among Students: Parallel Mediation Analysis - Afzal, Samra; Zamir, Shazia; Ali, Muhammad Asghar (Annals of Human and Social Sciences, 2024)
The purpose of present research is to find out the intricacies of imposter phenomenon, mental well-being, self-compassion and academic integrity interactions among university students through parallel mediation analysis. Imposter phenomenon (IP) is described as inner speech that creates self-doubt about own competency and beliefs, mental well-being of students is another serious concern of higher education organizations, self-compassion interventions helps to lower IP. Present research has cross-sectional non-experimental research design. The method used for collecting data was a survey through in-person visits and Google Form. 227 students of BS (Hons) took part as a sample of the research study. Results revealed that self-compassion and academic integrity fully mediate the relationship between imposter phenomenon and mental well-being. Workshops and training may be arranged to deal with imposters’ feelings. IP training may add discussion of contributors to IP in addition to strategies such as diffusion, mindfulness techniques, cognitive restructuring, and goal setting for dealing with impostor experiences. Academic Integrity, Imposter Phenomenon, Mental Well-Being, Parallel Mediation Analysis, Self-Compassion